Nudges, boosts, and sludge: Using new behavioral approaches to improve tax compliance - James Alm; Lilith Burgstaller; Arrita Domi; Amanda März; Matthias Kasper (Economies, 2023)
This paper discusses current developments in tax compliance research, with a focus on three aspects. First, we summarize empirical evidence on the traditional deterrence or enforcement approach, suggesting that tax audits and fines for noncompliance are critical in taxpayers' compliance decisions. However, recent research indicates that the effects of deterrence are more nuanced than initially thought, suggesting that other interventions are needed to improve tax compliance. Second, therefore, we discuss research on behavioral approaches to increase tax compliance, starting with research that analyzes the effects of 'nudges', or interventions that use behavioral economics to alter the ways in which the choice architecture facing individuals is communicated to them by the tax administration. As applied to tax compliance, we conclude that nudges have had mixed effects on increasing tax compliance, suggesting that the specific design and implementation of these interventions determine their effectiveness. Third, we extend our discussion to other behavioral economics interventions that have not yet been studied widely in tax compliance research. These include 'sludge', or institutional features that complicate compliance, and 'boosts', or initiatives that target individuals' competencies and thereby help them to make better decisions. Our central argument is that all three of these behavioral interventions should be utilized in the design of tax policies. However, for these methods to effectively complement traditional deterrence approaches, tax administrations should evaluate them before implementing them in the field. Closer cooperation between administrators and academics should thus be facilitated and encouraged.
Keywords: 330; tax compliance; deterrence theory; behavioral economics; nudges; boosts; sludge